“Ignorance of the law excuses no one:” Fundamental Laws Every Filipino Teachers in Educational Institutions Should Know - Cada, Jr., Leonardo F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In the Philippines, everyone is presumed to know the law. Laws in the Philippines take effect after fifteen days following the completion of their publication either in the Official Gazette or in a newspaper of general circulation in the Philippines. Respondents in this mini research were local teachers and professors from secondary and tertiary levels within the National Capital Region (NCR) with some of them from outside the NCR. Survey questionnaires were administered in this study through convenient and snowball sampling techniques. The initial pulse from the respondents indicated that they have a good percentage of the knowledge of the six identified laws. Most of their knowledge were acquired in attending seminars and conference.